Bibliotherapy: Awareness and Use among Medical Library Workers in Ogbomoso - Olajide John Abiola; Adebola Aderemi Olatoye (JINAV: Journal of Information and Visualization, 2023)
The concept of bibliotherapy draws upon various academic fields, such as medicine, literary criticism, librarianship, and psychology, to promote the use of reading as a therapeutic tool. This study aimed to explore the extent to which medical library workers are aware of and utilize bibliotherapy. Using a descriptive survey design, the study employed Slovin's formula and simple random sampling to select 24 respondents from a population of 45 medical library workers. The findings revealed that the medical library workers had a good understanding of bibliotherapy. Therefore, it is recommended that they should be equipped with the necessary skills to provide bibliotherapy services, and given the opportunity to practice it.